An analysis of some evidential structures in essays written by students of French as a foreign language. (April 2015) - Miche, Elisabeth
In this article, we perform an evidential analysis of three types of construction taken from essays written by students of French as a foreign language: the shown source, the quoted source and borrowed knowledge. The issue with these constructions, which refer to passages from a book, is knowing the extent to which they have an evidential value because, within the context of our analysis, the source and the knowledge reference overlap. We defend an evidential reading of these segments given their argumentative function in the students' discourse. We perform a pragmatic analysis of these language forms that take into account the parameters of the communicative situation and the type of text that the students have to produce. Our hypothesis is this: the figure of the teacher (who, in this case, is the hearer and the addressee) and his or her instructions have a direct impact on the way in which the student presents his or her knowledge of the book on which he or she is commenting. The analysis of the function of these three forms has also led us to address the issue of the relationship between evidentiality and notions like the reliability and epistemic modality. We conclude that source (evidentiality) is a reliability's character and an epistemic function in the discourse.